Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Time Token Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas Xl SMK N 1 Siatas Barita Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Leonardi Pandiangan; Pestaria Naibaho; Simion Harianja; Albiner Siagian; Oktober Tua Aritonang (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The purpose of this research is to determine the effect of using the Time Token Type Cooperative Learning Model on the Active Learning of Christian Religious Education Students in Class XI of SMK Negeri 1 Siatas Barita. The research method used is a quantitative method and this type of research is pre-experimental design in the form of "One Shot Case Study". The population is all students at SMK Negeri 1 Siatas Barita Class XI who are Protestant Christians, 422 people and a sample of 33 people was determined using the Purposive Sample technique. Data was collected using an observation sheet with 15 items for variable North Tapanuli Regency for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.544 > rtable(α=0.05,n=33) = 0.344. b) Testing a significant relationship obtained tcount= 3.607 > ttable(α=0.05, dk=n-2=31)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 29.6%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(α=0.05, dk numerator k=15, dk denominator=n-2=33-2=31) namely 13.01 > 1.62. Thus Ha is accepted and H0 is rejected.